How Politics Become Personal: Sociohistorical Events and their Meanings in People's Lives. (June 2015) - Stewart, Abigail J.; Winter, David G.; Henderson‐King, Donna; Henderson‐King, Eaaron; Hunter, Andrea G.; Stewart, Abigail J.
<x xml:space="preserve">Abstract</x> Major social and political events occurring in adolescence and young adulthood can create politicized identities in particular age cohorts, but within a generation, the experiences and results may differ as a function of different social identities based on (for example) race and gender. We explore the recollections in middle age of experiences in adolescence and young adulthood of four 1968 high school graduates, one from each intersection of race (African American and White) and gender. Most were strongly affected by the civil rights and women's movements, and the Vietnam War—but in ways that reflected both commonalities and distinctive features. The results support existing theories of generational identity and intersectionality, while at the same time suggesting more fine‐grained questions for future research.